Nilai-nilai Pendidikan dalam Munasabah Al-Qur’an - Abdul Hafiz Alfatoni (PALAPA, 2021)
Science Munasabah alqur'an is one of the sciences that play an important role when wanting to interpret the alqur'an, because with it we can know the correlation between verses and hungan between letters. This paper aims for us to be able to know and so that we can understand the understanding of reasonable, procotracted importance of munasabah, various munasabah, urgency of reasonable alqur'an and the values of education that exist in the sense of alqur'an. The research method used is literature research (libray reseach) which is research by collecting various kinds of data obtained from books that are used as data sources. Understanding reasonableness makes it easier for us to recite the Qur'an either with regard to the correlation between verses one with another or correlation between surahs. Munasabah Alqur'an is a correlation between verses, sentences and letters that exist in the Qur'an divided into five kinds, and has a very important role when wanting to understand the meaning in the Qur'an. Musanabah Alqur'a also plays an important role in the obligation in carrying out the teaching and learning process as well as how to improve the ability of teachers in teaching.